LEADING SUSTAINABILITY: VIEWS FROM AN OUTGOING USM-CGSS EXPERT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 25 March 2016 – After being in service at Universiti Sains Malaysia (USM) and the USM Centre for Global Sustainability Studies (CGSS) for the past seven years, it is now time for Professor Dr Kanayathu Chacko Koshy, 68, to bid farewell to the post which has helped USM to be recognised as a major player in addressing issues relating to sustainability issues through educational approaches.